Relationships between coinfection with cowpea aphidborn mosaic and cucumber mosaic viruses and yield of cowpea lines with varying resistance to these viruses - Mih, A.M.; Atiri, G.I.; Thottappilly, G. (1991)
The effect of mixed infection of cowpea aphid-borne mosaic (CAMV) and cucumber mosaic (CMV) viruses on cowpea yield varied with the resistance levels of cowpea lines, since there was a strong interaction between the latter and virus infection types atP ≤ 0.01. In cowpea line TVu 3629, with low resistance to both viruses, mixed infection significantly(P ≤ 0.05) reduced most yield components as compared with single infections and uninoculated controls. However, in line TVu 15656, which is highly resistant to both viruses, the effect of mixed infections was not significantly different from that of single infections or from the control. Between these two extremes were cowpea lines TVu 13683 and TVu 410, which were mildly resistant to CMV and CAMV, respectively; single infections significantly reduced the yield components relative to control, although these were generally not different from mixed infections. CMV, hitherto considered to be not economically important in cowpea in Nigeria, could induce severe yield losses when present in mixed infection with CAMV in cowpea lines with low resistance to both viruses. However, since mixed infection did not affect the yield of the highly doubly-resistant TVu 15656 cowpea line, it may be possible to breed for combined resistance to both viruses.